DEVELOPMENT OF THE LANDSCAPE GENRE OF PAINTING IN EUROPEAN COUNTRIES (Proceedings of International Educators Conference, 2024)
In Europe, the development of the landscape genre in painting developed in very intense stages, and it is no exaggeration to say that the creative works and works of the artists who created it served as a school for the creative artists of the world. The works of artists who created in the landscape genre have lost their importance to this day.